GEOCHEMICAL INDICATORS OF PALEOCLIMATE CHANGES IN SEDIMENTS OF LAKE BAIKAL - Goldberg E.L.; Fedorin M.A.; Grachev M.A.; Zolotarev K.V.; Khlystov O.M. (My University, 2001)
An X-ray fluorescent analysis with synchrotron radiation (SR-XFA).and neutron-activation analysis (INAA) were used to interpret high-resolution geochemical records of paleoclimate signals in bottom sediments of Lake Baikal. Concentrations of some elements and their ratios respond to climate change and thus mark glacial and interglacial stages. Sr/Ba, Sr/Rb, Sr/Cs, Sr/Ti, U/Th, Zn/Nb, U, Mo, Br, Eu, Tb, and Yb show positive correlations with the content of biogenic silica (Sibi), which is high in the periods of interglacials and low in those of glacials, whereas Ba, Rb, Cs, Th, La, Ce, Nd, and La (Ce, Ba)/Yb (Y, Zr) anticorrelate with Sibi, and increased concentrations of these elements mark glacial stages. The two series of geochemical signals, along with biogenic silica, reflect climate fluctuations from glacials to interglacials through the past 780 ka.